2019
DOI: 10.3390/molecules24224079
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Characterization and Discovery of Chemical Markers for Discrimination of Xanthii Fructus by Gas Chromatography Coupled to Mass Spectrometry

Abstract: Xanthii Fructus (XF) is known as a medicinal plant. It has been used as a traditional medicine because of its high biological efficacy. However, there have been few comprehensive studies on the specific chemical composition of the plant and consequently, the information is lacking for the mechanism of the natural product metabolites in humans. In this study, an efficient analytical method to characterize and discriminate two species of Xanthii Fructus (Xanthium canadense Mill. and Xanthium sibiricum Patrin ex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
(39 reference statements)
2
2
0
Order By: Relevance
“…Elaidic acid (18:1n‐9 t ) was the most abundant monounsaturated fatty acid found in the P. sanctopaulensis hexane fraction, 133.68 ± 6.32 μg/g. Although trans ‐unsaturated fatty acids are rare in nature, elaidic acid was previously described in Asteraceae species 52,53 . Linoleic acid (18:2n‐6c), comprised the major polyunsaturated fatty acid found in this analysis 454.04 ± 17.34 μg/g, this acid was previously described from Eupatorium 51 …”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…Elaidic acid (18:1n‐9 t ) was the most abundant monounsaturated fatty acid found in the P. sanctopaulensis hexane fraction, 133.68 ± 6.32 μg/g. Although trans ‐unsaturated fatty acids are rare in nature, elaidic acid was previously described in Asteraceae species 52,53 . Linoleic acid (18:2n‐6c), comprised the major polyunsaturated fatty acid found in this analysis 454.04 ± 17.34 μg/g, this acid was previously described from Eupatorium 51 …”
Section: Resultssupporting
confidence: 55%
“…Although trans-unsaturated fatty acids are rare in nature, elaidic acid was previously described in Asteraceae species. 52,53 Linoleic acid (18:2n-6c), comprised the major polyunsaturated fatty acid found in this analysis 454.04 ± 17.34 μg/g, this acid was previously described from Eupatorium. 51…”
Section: Identification Of Fatty Acids In the Hexane Fraction By Gas ...supporting
confidence: 52%
“…Once isoquercitrin is added, the new Q-marker system can distinguish Eucommiae Folium from Pyrrosiae Folium or Xanthii Fructus. Accumulated literature suggested that the latter two contain no isoquercitrin [43][44][45]. Therefore, it can recognize the possible counterfeit during the manufacture of Eucommiae Folium products.…”
Section: Resultsmentioning
confidence: 99%
“…sibiricum (Patrin ex Widder) Greuter (X. strumarium) (Family Asteraceae), also called Cocklebur or Xanthii Fructus, is a CHM. X. strumarium has multiple pharmacological activities including the antiviral activity (Guo et al, 2013;Lin et al, 2014;Shi et al, 2015;Amin et al, 2016;Jiang et al, 2017;Fan et al, 2019;Kim et al, 2019;Xia et al, 2020a;Xia et al, 2020b;Yuan, 2020). As a traditional Chinese herbal medicine, Pueraria montana var.…”
Section: Introductionmentioning
confidence: 99%